UWAGI NA TEMAT „RYTUAŁÓW OFIAROWANIA” I SZTUKI PERFORMANCE - Męderowicz, Jolanta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
We cannot mention the role of representations or rather appropriation of forms of ritual gestures in the space of contemporary art. There appear to be important in particular, references to the category of rites of sacrifice, symbolically encoded by neoawangardę especially the 60s and 70s, on the basis of clear statements and actions of Polish performance artists. “Ritual” and “performance” are the leading categories that namaściły, not only semantically, post-modernist vision of culture. However, as shown by numerous examples of performance art, the artists use this cultural pattern usually in order to resume a discussion on man, the role of the artist and the art in the era of the so-called liquid postmodernity, and to expose its demons. Performance artists repeatedly emphasized that performance cannot be a modern ritual in any sense because by its very nature it is opposed to any ritualisation. The purpose of artists of performance art has always been a manifestation of individuality and creative freedom and undermining any cultural stereotypes and clichés.